Lagos: Ownership and Identities Brochure - Lawanson, Taibat; Eleshin, Abisoye (Lagos Ownership and Identities (Intellectual Debates and One Month Photography Exhibition), 2023)
Brochure containing essays on Lagos
Keywords: History; Migration; African Studies; Lagos; Knowledge